Persepsi Masyarakat Terhadap Pusat Kesejahteraan Sosial Di Desa Sukamanah Kecamatan Cugenang Kabupaten Cianjur: Jurnal Ilmiah Pekerjaan Sosial Vol. xx No. x, Agustus 2022 - Victoria, Abigail; Rusmana, Aep; Yaneri, Ahmad (Politeknik Kesejahteraan Sosial Bandung, 2023)
Research on people's perceptions of the Social Welfare Center is motivated by differences in the views of experts regarding the Social Welfare Center, so it can also happen in the community about their views on this matter. The purpose of this study is to obtain an overview of people's perceptions of the Social Welfare Center which consists of three aspects, namely the knowledge aspect, the understanding aspect, and the assessment aspect. The method used in this study is a descriptive method with a quantitative approach. The population targeted in this study was the people of Sukamanah Village aged 20-65 years with a total of 3,478 respondents. Sampling used a simple random sampling technique to produce a sample of 97 respondents. Questionnaire data collection techniques and documentation studies with likert scale measuring instruments. Validity testing using advance validity and reliability test using Cronbach Alpha. The results showed that people's perception of the Social Welfare Center was in the moderate category (54.56%). There is a problem in the public perception of the Social Welfare Center in the assessment aspect is in the low category (34.55%) because the knowledge aspect is in the medium category (56.31%), and the understanding aspect is in the medium category (65.05%). Therefore, the researcher proposed a program